POETICS OF AUTOBIOGRAPHICAL MEMORY IN RAY BRADBURY’S NOVEL “DANDELION WINE”: ON THE WAY TO AN IMPRESSIONISTIC NOVEL - Anna A. Stepanova; Liudmyla S. Dushatska (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The focus of this article is on the peculiarities of autobiographical memory images representation in the literary piece. The purpose of this work is to research the poetics of autobiographical memory in Ray Bradbury`s novel Dandelion Wine. To conduct the research biographical, hermeneutic, historico-literary, and comparative-historical methods of analysis were applied. The poetics of autobiographical memory is represented by the set of artistic means used to render the author`s reminiscences and it combines the work`s autobiographical and autopsychological concepts seen as sort of eventual autobiographism and psychological autobiographism. The poetics of autobiographical memory is based on internal psychological kindredness of the author and the hero in the autobiographical work. In Ray Bradbury`s writing autobiographism of events is frequently superseded by psychological one, engaging the mechanisms of autobiographical memory at the level of sensory impressions, emotional states, spiritual associations, defining the peculiarity of autobiographical poetics. The retrospective manner of narrative in the novel reveals two planes of autobiographical memory of the writer, which are represented by both the biographical plane, which manifests itself as factual data, including the names of those close or dear to the author, the names of the real places, locations, events and so on, and the autopsychological plane, used for recreation of the author`s own childhood emotions, which Ray Bradbury defined as “sense impressions”. The purposeful work of the writer`s memory aimed at carefully preserving his own impressions with their subsequent reproduction in the piece can be clearly seen in the vivid expression of the author`s images of experiences and perceptions, brought back to life in the novel. In Dandelion Wine`s text the sensory impressions recalled by Bradbury are transformed into the system of metaphoric images demonstrating the plasticity of representation and visual effect. Each impression acquires its unique plastic image. Conclusion. The poetics of autobiographical memory in the novel Dandelion Wine finds its expression in the depiction of the writer`s memories about his childhood sensory impressions, feelings and perceptions. The main principles of the novel`s poetics are the fragmentary narrative; time, split into a series of moments; the use of stream of consciousness method, actualized through inner monologues of the hero; expression of reminiscences in visual plastic images, sensory impressions, feelings, associations, conveyed through metaphorically exquisite lyrical style of narrative, suggesting that Bradbury follows the tradition and experience of impressionistic aesthetics of Proust, giving to Dandelion Wine the form of impressionistic novel. The principles of autobiographical poetics applied in the novel, appear as the stylecreating principles of the poetics of impressionistic novel genre in literature.